Triglyceride-glucose index as a marker for visceral obesity in patients with gastric cancer - Zuo, Junbo; Huang, Zhenhua; Ge, Yan; Ding, Xin; Wang, Xiuhua; Huang, Yan (Frontiers in Nutrition, 2025)
BackgroundThe triglyceride-glucose (TyG) index has emerged as a validated and cost-effective indicator of insulin resistance (IR). Given the significant association between visceral obesity and IR, this study aimed to investigate the utility of the TyG index in estimating visceral obesity in patients with gastric cancer (GC).MethodsThe visceral fat area (VFA), subcutaneous fat area (SFA), and VFA-to-SFA ratio (VSR) were determined through the analysis of CT images at the lumbar 3 level. The definition of visceral obesity was established as VFA ≥ 100 cm2. The association between the TyG index and visceral obesity was assessed using logistic regression analysis and restricted cubic splines. The diagnostic performance for identifying visceral obesity was evaluated by calculating the area under the Receiver Operating Characteristics curve (AUC).ResultsThe cross-sectional study enrolled a total of 314 patients with GC, among whom 159 (50.64%) were identified as having visceral obesity. The TyG index was positively correlated with VFA (r = 0.45, p < 0.001), SFA (r = 0.23, p < 0.001), and VSR (r = 0.35, p < 0.001). However, subsequent multivariate linear regression analysis demonstrated that the TyG index was significantly associated with VFA and VSR, but not SFA. After adjusting for potential confounding factors, the TyG index remained independently associated with visceral obesity (OR = 2.54, 95% CI: 1.32–4.89, p = 0.005) and demonstrated a significantly positive linear correlation with visceral obesity in patients with GC (p-value for non-linearity = 0.116). TyG-BMI, the combination index of TyG and BMI, showed the highest predictive power in identifying visceral obesity in GC patients (AUC = 0.849, 95% CI: 0.807–0.890, p < 0.001). The subgroup analysis revealed a significantly stronger positive association between the TyG index and visceral obesity in patients with BMI ≥ 25 kg/m2 (p for interaction = 0.049).ConclusionThe TyG index exhibited a significant association with visceral obesity and proved to be a valuable predictor for visceral obesity when combined with BMI in patients with GC.